Advancing Nuclear Energy Governance Through Strategic Pathways for Q-NPT Adoption - Hassan Qudrat-Ullah (Energies)
This paper proposes a strategic framework to enhance nuclear energy governance by advancing the Qudrat-Ullah Nuclear Peace and Trust (Q-NPT) framework. Designed to complement existing treaties such as the Nuclear Non-Proliferation Treaty (NPT) and International Atomic Energy Agency (IAEA) safeguards, Q-NPT integrates principles of equity, transparency, and trust to address persistent governance challenges. The framework emphasizes sustainable nuclear technology access, multilateral cooperation, and integration with global energy transition goals. Through an analysis of institutional, economic, technological, and geopolitical barriers, the study outlines actionable pathways for adoption, including legal harmonization, differentiated financial instruments, and deployment of advanced verification technologies such as blockchain, artificial intelligence (AI), and remote monitoring. A phased implementation timeline is presented, enabling adaptive learning and stakeholder engagement over short-, medium-, and long-term horizons. Regional case studies, including Serbia and Latin America, demonstrate the framework’s applicability in diverse contexts. By linking nuclear policy to broader climate, energy equity, and global security objectives, Q-NPT offers an operational and inclusive roadmap for future-ready governance. This approach contributes to the literature on energy systems transformation by situating nuclear governance within a sustainability-oriented, trust-centered paradigm.